Highly conductive graphene by low-temperature thermal reduction and in situ preparation of conductive polymer nanocomposites - Yee, Wu Aik (2013)
Polydopamine-coated graphene oxide (DGO) films exhibit electrical conductivities of 11 000 S m−1 and 30 000 S m−1 upon vacuum annealing at 130 °C and 180 °C, respectively. Conductive poly(vinyl alcohol)/graphene and epoxy/graphene nanocomposites show low percolation thresholds due to the excellent dispersibility of the DGO sheets and their effective in situ reduction.